2020
DOI: 10.21608/edj.2020.41265.1239
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Single Versus Multiple Intra-Articular Injection of Synovial Fluid Mesenchymal Stem Cells on Rat Temporomandibular Joint With Induced Arthritis. Biochemical and Histologic Analysis

Abstract: Introduction: Osteoarthritis (OA) is the most common chronic musculoskeletal disorder. Nowadays, the role of synovial fluid mesenchymal stem cells (SF MSCs) is increasingly attributed to the treatment of Temporomandibular joint osteoarthritis. This study aimed to compare single versus multiple intra-articular injection of SFMSCs in terms of macroscopic, biochemical, and histological analysis. Material & methods: 18 young adult male 200-300 grams albino rats were used in the current study divided randomly into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Additionally, TNF-α is up-regulated in collagen and aggrecan cartilage destruction in joints affected by rheumatoid arthritis and is responsible for necroptosis in injured and inflamed tissue [ 220 ]. Some animal studies showed decreasing of TNF-α in synovial fluid after repeated MSCs application [ 221 ] as well as in other tissues [ 222 , 223 , 224 ]. IFN-γ is a product of T-cells and NK-cells and its concentrations in synovial fluid are higher in patients with severe OA and cartilage defects [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, TNF-α is up-regulated in collagen and aggrecan cartilage destruction in joints affected by rheumatoid arthritis and is responsible for necroptosis in injured and inflamed tissue [ 220 ]. Some animal studies showed decreasing of TNF-α in synovial fluid after repeated MSCs application [ 221 ] as well as in other tissues [ 222 , 223 , 224 ]. IFN-γ is a product of T-cells and NK-cells and its concentrations in synovial fluid are higher in patients with severe OA and cartilage defects [ 90 ].…”
Section: Discussionmentioning
confidence: 99%